2016
DOI: 10.1063/1.4960691
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue effect on polarization switching dynamics in polycrystalline bulk ferroelectrics

Abstract: Statistical distribution of switching times is a key information necessary to describe the dynamic response of a polycrystalline bulk ferroelectric to an applied electric field. The Inhomogeneous Field Mechanism (IFM) model offers a useful tool which allows extraction of this information from polarization switching measurements over a large time window. In this paper, the model was further developed to account for the presence of non-switchable regions in fatigued materials. Application of the IFM-analysis to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
(206 reference statements)
0
13
0
Order By: Relevance
“…Before concluding, it should be emphasized that the present study has once again demonstrated that the outstanding piezoelectric properties of tubular arrays in particular and ferroelectrets in general originate from a unique combination of mechanical and electrical properties of polymer structures with voids. On the one hand, polymer dielectrics with air cavities can accumulate a quasi-remanent polarization with relatively low charge density up to approximately 0.1 µC/cm 2 22 , 27 , 37 39 , 46 significantly lower than the typical values for classical bulk ferroelectric polymers (5–15 µC/cm 2 ) 7 , 47 and conventional piezoceramics (10–100 µC/cm 2 ) 6 , 48 , 49 . But on the other hand, ferroelectrets, like all porous polymers 1 , 50 , have an extremely low Young modulus ranging from 0.2 MPa to 10 MPa, depending on the mechanical properties of the polymer matrix and the pore geometry 10 , 22 , 30 , 33 , 44 , 51 .…”
Section: Resultsmentioning
confidence: 93%
“…Before concluding, it should be emphasized that the present study has once again demonstrated that the outstanding piezoelectric properties of tubular arrays in particular and ferroelectrets in general originate from a unique combination of mechanical and electrical properties of polymer structures with voids. On the one hand, polymer dielectrics with air cavities can accumulate a quasi-remanent polarization with relatively low charge density up to approximately 0.1 µC/cm 2 22 , 27 , 37 39 , 46 significantly lower than the typical values for classical bulk ferroelectric polymers (5–15 µC/cm 2 ) 7 , 47 and conventional piezoceramics (10–100 µC/cm 2 ) 6 , 48 , 49 . But on the other hand, ferroelectrets, like all porous polymers 1 , 50 , have an extremely low Young modulus ranging from 0.2 MPa to 10 MPa, depending on the mechanical properties of the polymer matrix and the pore geometry 10 , 22 , 30 , 33 , 44 , 51 .…”
Section: Resultsmentioning
confidence: 93%
“…As a result, in the macroscopic level, asymmetric strain curve with two different strain states is observed under bipolar loading. 11,16 Though high strain memory is desired, its stability is more concerned. However, if an negative field with half the value is applied, a partially depoled state with more random redistributed domain state would be obtained, leading to a much smaller P r À (B 0 ) than that of B in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Maximum strain memory takes place when E À locates around E c À , which can be ascribed to the nearly fully depoled state with randomized domains. 11,16 Though high strain memory is desired, its stability is more concerned. Figure 3 compares the cycling stability of strain memory for Mn-doped PMS-PZT under electric signals with varying E À .…”
Section: Resultsmentioning
confidence: 99%
“…Any material behaviour can be expressed as a mathematical model when the second law of thermodynamics is fulfilled with suitable selection state variables, analytical expressions of the state potential and dissipative potentials [ 9 ]. Zhurkov et al [ 10 ] stated that physical mechanisms and apparent characteristics of fatigue depend on the structure of materials and physical conditions, chemical composition, and the kind of utilized load. They modified the inhomogeneous field mechanism (IFM) model for the development of distinct fatigue degradation.…”
Section: Introductionmentioning
confidence: 99%